Designing an Enterprise Risk Management Curriculum for Business Studies: Insights From a Pilot Program. Issue 1 (March 2014) - Acharyya, Madhu; Brady, Chris
Abstract The latest financial crises have highlighted the centrality of managing risks across organizations. Internationally, Basel II/III, The Volcker Rule of the Dodd–Frank Act, and Vickers' Ring‐Fence all propose stronger management of risk across banks and greater oversight of executive compensation to mitigate generic risk. Given this situation, it might be assumed that academia would also view risk as a central concern for its business programs. It seems not. There is a little evidence that academic curricula are being specifically designed to address this issue. This article examines an Enterprise Risk Management curriculum delivered to graduate student cohorts over 3 consecutive years. Four criteria were used to develop the new curriculum. First, it should take a holistic view of risk; second, the theories related to risk needed to be transformed from individual to group level; third, the dynamics of risk due to market factors needed to be understood; and finally, the way firms respond to crises needed to be observed and embedded in the curriculum.